NAn Analysis Of The Role Of Teachers In Literacy Activities To Improve Learning Interest Of Grade 3 Students Of SDN 1 Andalan In The 2024/2025 Academic Year - Sonia, Sonia; Alawiyah, Tuti; Marzoan, Lalu (JUPE : Jurnal Pendidikan Mandala, 2025)
This study focuses on the role of teachers in literacy activities to increase the learning interest of third-grade students at SDN 1 Andalan. This study aims to analyze the role of teachers in literacy activities to increase the learning interest of third-grade students at SDN 1 Andalan. The background of this research is based on the importance of the teacher's role as a facilitator, motivator, and guide in fostering students' interest in learning through structured and continuous literacy activities. This research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, in-depth interviews, and documentation. The subjects of this study were the school principal, third-grade homeroom teachers, and third-grade students at SDN 1 Andalan.The research results indicate that teachers play a very important or significant role in literacy activities, both as facilitators, mentors, and motivators. Literacy activities conducted include reading together, creative writing, and the use of engaging learning materials. The role of teachers in creating a pleasant learning environment and incorporating literacy values into instruction will undoubtedly have a positive impact on increasing students' interest in learning. Supporting and hindering factors include the availability of appropriate reading materials, school support, and teachers' creativity in designing literacy activities. Hindering factors include time constraints and insufficient parental involvement.